Measuring the Impact of Product Mix Heterogeneity on Manufacturing Overhead Cost. - Anderson, Shannon W. (The Accounting Review, 1995)
Examines the impact of product mix heterogeneity (PMH) on manufacturing overhead costs (MOHC) in three plants of a textile firm. Adaption of an approach for measuring PMH; Identification of seven forms of PMH for woven fabrics; Difficulties in establishing the relationship between variable MOHC and PMH using time series data.